The Impact of Supervised Physical Activity in Urban Green Spaces on Mental Well-Being Among Middle-Aged Adults: A Quasi-Experimental Study - Zhengyang Xu; Federica Moro; Niccolò Baldoni; Mario Mauro; Sofia Marini; Laura Bragonzoni; Laura Dallolio; Erika Pinelli; Raffaele Zinno; Gerardo Astorino; Giacomo Prosperi; Pasqualino Maietta Latessa; et al. (Urban Science)
In recent decades, extensive evidence has indicated that green spaces and physical activity (PA) are associated with mental health, while limited research has explored the combined effects of supervised PA in urban green spaces. To address the research gap, this study examines whether supervised PA within green spaces improves mental health among middle-aged adults (45–65 years) through a quasi-experimental longitudinal study developed as part of the “Moving Parks” project in Bologna, Italy. Using the Italian version of the Warwick–Edinburgh Mental Well-being Scale (WEMWBS), mental health was measured at pre- and post-assessment. A total of 340 participants (258 intervention, 82 control) were included in the study. The effects of intervention, group assignment, and their interaction on mental health scores were analysed using a two-way repeated measures ANOVA. No significant differences in mental health improvements were observed between the intervention group and control group. The results indicated significant main effects of time on total WEMWBS scores and several subscales such as optimism, usefulness, energy, and cheerfulness, but these changes were not significantly influenced by group assignment. The only significant group-by-time interaction was found in perceived usefulness. These findings do not provide conclusive support for the hypothesised benefits of the supervised PA intervention. Possible explanations include seasonal variation, baseline or ceiling effects, and the potential limitations of the WEMWBS in detecting short-term psychological changes. Future research should consider extending intervention duration, improving group comparability, and employing more sensitive assessment tools to better evaluate the mental health impact of green space–based PA programmes.